Representaciones sociales de los vendedores ambulantes frente al habitante de calle en el Malecón Bahía de la cruz de Buenaventura (2024)
The objective of this thesis was to understand the social representations of street vendors in front of street dwellers on the Malecón Bahía de la Cruz in the city of Buenaventura – Valle del Cauca. For the development of the research, the theory of social representations of Moscovici and Abric was taken as a reference. The qualitative phenomenological approach was defined as a methodology, which recognizes the interpretation of the facts in order to capture the meaning of the phenomena and the intention of the activities (Moustakas, 1994). Therefore, a survey and semi-structured interview were applied to 3 street vendors to then be triangulated and analyzed. Finally, a contextualized and enriching vision is offered that allows us to understand the social representations of street vendors and street dwellers on the Malecón Bahía de la Cruz in the city of Buenaventura – Valle del Cauca.